Diesel fuel derived from vegetable oils, VI: Specifications and quality control of biodiesel - Mittelbach, M.
Due to the rising importance of biodiesel as alternative fuel in many countries, it is absolutely necessary to establish standards for the description of the quality of the product. The parameters and the corresponding threshold values defining the quality of rapeseed-oil methyl esters (RME)used as biodiesel according to the latest Austrian standardization (O-NORM)are presented and discussed. The difference is distinguished between general fuel parameters, which already exist for mineral diesel fuel, and vegetable-oil-specific parameters, which have to be additionally defined. Correlations between parameters like Conradson carbon residue, sulfate ash and phosphorus content are outlined. Problems concerning the inclusion of parameters, which have not yet been taken up in the Austrian standards, like iodine number and water content, are discussed. In the second part, analytical aspects for the determination of free and bonded glycerol, as well as mono-, di- and triglycerides are described. Well tested methods for the analysis of glycerol and glycerides are presented, including the desctiption of the advantages and disadvantages of each method.
Keywords: VEGETABLE OILS; DIESEL FUEL; ANALYSIS; STANDARDIZATION